The Impact of Government Policies on The Competitiveness of Clove Commodity in Tolitoli Regency: Multi Period PAM Approach - Adnan Putra Pratama; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2020)
This study aims to determine the competitiveness of clove commodities in Tolitoli Regency in terms of competitive and comparative advantages and to determine the impact of government policies on the sustainability of clove farming in Tolitoli Regency. The method of determining respondents using a simple random sampling method and obtained as many as 87 samples of clove farmers. The data analysis method used is the Multi-Period PAM (Policy Analysis Matrix). The results of this study indicate that the clove commodity in Tolitoli Regency has competitiveness in terms of competitive and comparative advantages with a PCR value of 0.415 and DRCR 0.412. The impact of government policies on the output of clove farming in Tolitoli is protective against farming systems with an NPCO value of 1.088, but tends to be weak. While on the other hand, the impact of government policies on clove farming inputs is unprotective with an NPCI value of 1.061, meaning that farmers have not received positive incentives from the current input subsidy policy. The impact of government policies on input-output as a whole is protective and provides positive incentives to farmers, but the value of the coefficient shows the level of protection that is still relatively weak and very vulnerable if there is a change in policy. The regional government is expected to provide protection to clove farmers in the form of setting the cost of clove purchases and also to exercise strict supervision of cartel practices in the clove trade system.